2017
DOI: 10.17058/reci.v7i2.7731
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias de adesão à higienização das mãos por profissionais de saúde

Abstract: Justificativa e Objetivo: As infecções relacionadas à assistência em saúde constituem séria ameaça à saúde de pacientes hospitalizados e contribuem para aumentar as taxas de mortalidade e morbidade. A higienização das mãos é a medida individual mais simples e de menor custo com vistas a prevenir a disseminação das infecções em serviços de saúde. Mediante o exposto, o estudo busca analisar as publicações relacionadas às estratégias utilizadas para aumentar a adesão dos profissionais de saúde à higienização das … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
1
3
0
12
Order By: Relevance
“…Still in relation to the practice of hand hygiene, it was observed that in many rooms there were no sinks, or they were not functioning. In the same direction of the present study, another study revealed that even though there were satisfactory hand washing sinks and dispensers, they often did not have good conditions of use and managers did not know these difficulties (16) .…”
Section: In a Prenatal Consultation Nurse Does Not Wash Hands Takes supporting
confidence: 59%
“…Still in relation to the practice of hand hygiene, it was observed that in many rooms there were no sinks, or they were not functioning. In the same direction of the present study, another study revealed that even though there were satisfactory hand washing sinks and dispensers, they often did not have good conditions of use and managers did not know these difficulties (16) .…”
Section: In a Prenatal Consultation Nurse Does Not Wash Hands Takes supporting
confidence: 59%
“…Portanto, pode-se dizer que o uso das tecnologias educativas possibilitou a atualização dos profissionais sobre os temas propostos, bem como, o empoderamento dos mesmos para a resolução da problemática da IH no CTI (ARRAES JARDIM et. al, 2019;OLIVEIRA;PINTO, 2018, DE PAULA et. al, 2017CROTI;BATIGALIA, 2013).…”
Section: Metodologiaunclassified
“…Nesse contexto, é perceptível a importância de ações e práticas educativas em saúde, para os profissionais que atuam na linha de frente do atendimento médico-hospitalar, visando mudanças corretivas e preventivas nas práticas assistenciais realizadas pelos mesmos, assim como ao combate das IH (OLIVEIRA; PINTO, 2018, DE PAULA et al, 2017.…”
Section: Introductionunclassified
See 2 more Smart Citations